Rapid aerobic sludge granulation by short-term in-situ chitosan dosing: Performance, mechanism and microbial response - Fengfan Yu; Ruirui Wang; Yanhang Wang; Mengjie Qian; Jintao Sun; Jinwen Song; Jinte Zou; Jun Li (Bioresource Technology, 2026)

Trade-offs among pear yield, fruit quality, and reactive nitrogen losses under water–nitrogen management across contrasting soil textures - Yanlong Li; Ruirui Du; Mingde Sun; Yang Wu; Zhenxu Liang; Qinghua Wang; Jun Liu; Songzhong Liu (Journal of Environmental Management, 2026)

N and S co-doped graphene-based single-atom catalysts for highly efficient nitrate reduction - Jin-Hang Liu; Yu Sun; Xiaoduo Jiang; Huixiong Jiang; Ruirui Wang; Yawei Wang; Huixian Ye; Xiudong Chen; Li-Ming Yang (Fuel, 2026)

Novel mutation sites in yeast FAS enhance the production of C6–C10 fatty acids and their ethyl esters - Yupeng Wang; Junbao Gong; Xinyu Lu; Yanfang Chen; Ruirui Li; Ying Guo; Chunhong Sun; Xinjian Wang; Ying Zhou; Xiaole Wu; Yefu Chen (Food Bioscience, 2026)

Coupling heterovalent complementary doping with surface tailoring for stable O3-type layered oxide cathodes - Yang Liu; Haoji Wang; Yang Sun; Yingchang Yang; Wei Shi; Kaixu Yang; Jing Chen; Ruirui Wang; Xinyao Yang; Yanxu Wang; Haibiao Ning; Qifu Shi; et al. (Chemical Engineering Journal, 2026)

Super-resolution multimodal spatial transcriptomics reveals an ovoid stem cell niche structuring de novo shoot regeneration - Xiehai Song; Shaoman Zhang; Zhiliang Yue; Yongqi Liu; Shanshan Chen; Yani Niu; Yan Shi; Hengjia Yang; Jiahao Xu; Yuanyuan Miao; Meizhi Xu; Yingxue Zhou; et al. (Molecular Plant, 2026)

Bioactive earthworm proteins and peptides from traditional Chinese medicine: structural diversity, biomedical applications, and emerging biomanufacturing strategies - Hanzhi Weng; Fengling Yang; Zhiliang Hou; Siyan Zhou; Jie Lu; Xiaoyuan Sun; Ruirui Xu; Zhen Kang (Systems Microbiology and Biomanufacturing, 2026)

Mechanistic study of macrolide antibiotics degradation induced by plasma-generated hydroxyl radicals and hydrogen peroxide - Ruirui Sun; Yifan Liu; Xiaolong Wang; Shiji Zhang; Daoyuan Liu; Zongzheng Wang; Yadi Liu; Ying Sun; Tong Zhao; Yuantao Zhang (Process Safety and Environmental Protection, 2026)

Scalable ergothioneine production via integrating chemical methylation and rhodanese-catalyzed CS bond formation - Jie Lu; Xiaoyuan Sun; Hanzhi Weng; Weiquan Ding; Fengling Yang; Guochen Du; Ruirui Xu; Zhen Kang (Chemical Engineering Journal, 2026)

mRNA Rather than Protein Expression of Hepatic Selenoprotein H is More Sensitive to Short-term Low Aflatoxin B1 Exposure in Mice with Varying Selenium Intake - Ruirui Yu; Mengru Hao; Aiping Liu; Chenggang Yang; Ping Xu; Yong Zhou; Alexey A. Tinkov; Aolin Yang; Qingqing Lv; Ziyu Han; Chao Wang; Zhou Wang; et al. (Biological Trace Element Research, 2026)

Identification of quantitative trait loci qPL6 for petiole length in soybean - Weiwei Fan; Lindong Wang; Wenxuan Huang; Jia Liu; Bing Li; Jingyu Peng; Ruirui Ma; Ran Xu; Lianjun Sun (Theoretical and Applied Genetics, 2026)

Bacterial communities of rhizolith- and root-associated in the Tengeri Desert, China - Jian Chen; Qingfeng Sun; Ruirui Chen; Zhihao Zhang; Zhen Liu; Gongyou Chen (Rhizosphere, 2025)

Bimetallic chloride in situ etching of NiFe alloy substrate to synthesize porous coral structure catalyst for efficient oxygen evolution reaction - Yu Zhang; Yaoxia Yang; Biaobiao Lu; RuiRui Zhang; Fuxing Zhou; Dongfei Sun; Qingtao Wang; Jian Li; Ziqiang Lei (Fuel, 2025)

Benchmark testing for 2H neutron cross section calculated using Faddeev equation - Huanyu Zhang; Haicheng Wu; Ruirui Xu; Ping Liu; Xiaofei Wu; Xiaodong Sun; Danyang Pang (Annals of Nuclear Energy, 2025)

Cornus officinalis polysaccharides nano-selenium exhibits anti-fatigue effects by regulating gut microbiota in mice - Jianrui Sun; Ruirui Ren; Jinglan Li; Jiaqi Fan; Linlin Yao; Shanshan Tie; Jie Zhang; Dahong Wang; Shaobin Gu (Food Bioscience, 2025)

Evaluation of the Degradation Effect of Zearalenone in feed by Bacillus amyloliquefaciens H6 and its Detoxification in Mice - Ruolin Wang; Kaiwei Geng; Yuxuan Liu; Yang Liu; Yujie Gong; Ruirui Jiang; Yadong Tian; Xiangtao Kang; Xiangli Sun; Yanbin Wang (Current Microbiology, 2025)

A genomic compendium of cultivated food-derived lactic acid bacteria unveils their contributions to human health - Hao Jin; Keyu Quan; Lijun You; Lai-Yu Kwok; Teng Ma; Yalin Li; Xuan Shi; Xin Su; Ruirui Lv; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2025)

Layered double hydroxides-engineered biochar for selective phosphate recovery by flow-electrode capacitive deionization - Jingke Song; Xin Zhao; Ruirui Liu; Songsong Zhi; Ruixue Han; Jiangzhou Xie; Jianhui Sun; Kai Jiang; Dapeng Wu (Journal of Environmental Chemical Engineering, 2025)

An innovative process for two-step leaching calcium from steel slag and capturing CO2 to synthesize spindle-shaped CaCO3 - Min Gan; Lincheng Liu; Zengqing Sun; Xiaohui Fan; Zitan Gao; Zhiyun Ji; Ruirui Yuan; Yufeng Wu; Xiaolong Wang; Hao Lv; Yuncan Cao (Process Safety and Environmental Protection, 2025)

The effect of stem contact fermentation on the quality of Cabernet Sauvignon and Merlot wines from Yantai, China - Ruirui Li; Dongyue Yang; Zhiyu Li; Xiaohong Tang; Ke Zhong; Yan Ding; Xiaomei Han; Xueqiang Guan; Yuxia Sun (Food Bioscience, 2025)

Innovative microbial activators for enhanced bioremediation of oil-contaminated soils: mechanistic insights - Yating Deng; Wujuan Sun; Yongbin Li; Jun Wei; Ruirui Rao; Qiongyu Cao; Sichang Wang; Qunzheng Zhang; Congyu Ke (World Journal of Microbiology and Biotechnology, 2025)

Carbonation pretreatment enhance the hydrothermal detoxification of municipal solid waste incineration fly ash - Ruirui Yuan; Xiaohui Fan; Min Gan; Zhiyun Ji; Zengqing Sun; Lincheng Liu; Xiaolong Wang; Jiaoyang Wei (Process Safety and Environmental Protection, 2025)

Development of recombinant antibody and application of colloidal gold Immunochromatography assay for rapid detection of zearalenone - Jiadi Sun; Yunyun Wang; Ting Zhang; Wancheng Ma; Yongli Ye; Jia Xu; Ruirui Dong; Yinzhi Zhang; Xiulan Sun (Food Bioscience, 2025)

Urea amidolyase displayed on the surface of Saccharomyces cerevisiae for ethyl carbamate reduction in Chinese Huangjiu - Yupeng Wang; Qingbo Deng; Fangyuan Liu; Qian Li; Ruirui Li; Huan Wang; Chunhong Sun; Xinjian Wang; Xiaole Wu; Yefu Chen (Food Control, 2024)

Perfluoroalkyl substances exposure and the risk of breast cancer: A nested case-control study in Jinchang Cohort - Qian Dou; Yana Bai; Yongjun Li; Shan Zheng; Minzhen Wang; Zhongge Wang; Jianyun Sun; Desheng Zhang; Chun Yin; Li Ma; Yongbin Lu; Lizhen Zhang; et al. (Environmental Research, 2024)

Exploring the impact of hyper-treated-quantity on the performance to access GHG emission in a full-scale A2O + MBR process: from predictions to implementation - Yongfeng Hu; Yongxiang Zhang; Ruirui Sun; Kun Wang; Qing Cai (Clean Technologies and Environmental Policy, 2024)

Construction of foam-like carbon microspheres with controllable pseudo-graphitic domains: Synergistic enhancement of K-ion adsorption/intercalation storage - Qingjuan Ren; Lei Yan; Xuewen Yu; Wenhua Lei; Zhongyu Sun; Ruirui Hao; Jianzeng Yang; Zhiqiang Shi (Chemical Engineering Journal, 2024)

Abnormal functional connectivity of the reward circuit associated with early satiety in patients with postprandial distress syndrome - Pan Zhang; Yangke Mao; Liangchao Gao; Zilei Tian; Ruirui Sun; Yuqi He; Peihong Ma; Beihong Dou; Yuan Chen; Xiabing Zhang; Zhaoxuan He; Tao Yin; et al. (Appetite, 2024)

Environmentally relevant exposure to cotinine induces neurobehavioral toxicity in zebrafish (Danio rerio): A study using neurobehavioral and metabolomic approaches - Dan Yang; Wenfei Yu; Jiajia Qu; Yuexing Shen; Jingtong Yu; Ruirui Meng; Zhen Tao; Jiangfei Chen; Wei Du; Haitong Zhe Sun; Yunhui Zhang; Yuanchen Chen; et al. (Environmental Pollution, 2024)

Identification of point and nonpoint emission sources of neonicotinoid pollution in regional surface water - Yuanchen Chen; Jun Ling; Wenfei Yu; Li Zhang; Ruxin Wu; Dan Yang; Jiajia Qu; Hangbiao Jin; Zhen Tao; Yuexin Shen; Ruirui Meng; Jingtong Yu; et al. (Water Research, 2024)

Using UAV-based multispectral remote sensing imagery combined with DRIS method to diagnose leaf nitrogen nutrition status in a fertigated apple orchard - Guangzhao Sun; Tiantian Hu; Shuaihong Chen; Jianxi Sun; Jun Zhang; Ruirui Ye; Shaowu Zhang; Jie Liu (Precision Agriculture, 2023)

Food-borne botulism from homemade sauce leading to cardiac arrest: A family case series with literature review - Weiying Yang; Dongyue Jiang; Ruirui Li; Lichao Sun (Toxicon, 2023)

A large-scale comparative genomics study reveals niche-driven and within-sample intra-species functional diversification in Lacticaseibacillus rhamnosus - Lijun You; Ruirui Lv; Hao Jin; Teng Ma; Zhixin Zhao; Lai-Yu Kwok; Zhihong Sun (Food Research International, 2023)

Intraspecific microdiversity and ecological drivers of lactic acid bacteria in naturally fermented milk ecosystem - Lijun You; Hao Jin; Lai-Yu Kwok; Ruirui Lv; Zhixin Zhao; Menghe Bilige; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2023)

Rapid discrimination of the identity of infant formula by triple-channel models - Nasi Ai; Ruirui Liu; Xuelu Chi; Zheng Song; Yiwei Shao; Yanmei Xi; Tong Zhao; Baoguo Sun; Jianbo Xiao; Jianjun Deng (Food Chemistry, 2023)

Grazing-induced cattle behaviour modulates the secondary production in a Eurasian steppe ecosystem - Lulu Hou; Xiaoping Xin; Haixia Sun; Yi Tao; Jiquan Chen; Ruirui Yan; Xiang Zhang; Beibei Shen; Ahmed Ibrahim Ahmed Altome; Yousif Mohamed Zainelabdeen Hamed; Xu Wang; Serekpaev Nurlan; et al. (Science of The Total Environment, 2023)

Quantifying climate and anthropogenic impacts on runoff using the SWAT model, a Budyko-based approach and empirical methods - Ruirui Xu; Dexun Qiu; Changxue Wu; Xingmin Mu; Guangju Zhao; Wenyi Sun; Peng Gao (Hydrological Sciences Journal, 2023)

Degradation of 2,4-Dichlorophenol Through Fenton Process Catalyzed by Nanoscale Zero-Valent Iron Supported by Biochar - Junlong Yu; Xiuxia Zhang; Ruojun Ma; Yi Du; Xiaodong Zhao; Shuai Zuo; Kangning Dong; Ruirui Wang; Yupeng Zhang; Yingying Gu; Juan Sun; Qiyou Liu (Water, Air, & Soil Pollution, 2023)

PCNA promotes PRRSV replication by increasing the synthesis of viral genome - Qiumei Wang; Heyou Yi; Yanchen Guo; Yankuo Sun; Zhiqing Yu; Lechen Lu; Ruirui Ye; Ermin Xie; Qianwen Wu; Yingwu Qiu; Weipeng Quan; Guihong Zhang; et al. (Veterinary Microbiology, 2023)

Subcritical hydrothermal treatment of municipal solid waste incineration fly ash: A review - Xiaohui Fan; Ruirui Yuan; Min Gan; Zhiyun Ji; Zengqing Sun (Science of The Total Environment, 2023)

Highly sensitive and quantitative fluorescent strip immunosensor based on an independent control system for rapid detection of tetrodotoxin in shellfish - Jiadi Sun; Zhixuan Shi; Ting Zhang; Liangzhe Wang; Ruirui Dong; Yinzhi Zhang; Xiulan Sun (Food Control, 2023)

Spatial–temporal dynamics of the built environment toward sustainability: A material stock and flow analysis in Chinese new and old urban areas - Dong Yang; Mengyuan Dang; Jing Guo; Lingwen Sun; Ruirui Zhang; Feng Han; Feng Shi; Qian Liu; Hiroki Tanikawa (Journal of Industrial Ecology, 2023)
The urban built environment has accumulated massive amounts of resources, which is the main “hot spot” of construction materials and energy consumption in cities. To effectively monitor and manage resources use and waste disposal toward sustainability, this study intended to explore different metabolic paths of the urban built environment, as well as strategies for new and old urban areas separately with the help of material stock and flow analysis. Based on snapshots of 2003, 2010, and 2017 and combined with big data, a four‐dimensional geographic information system buildings database of Lixia District in Jinan, China, was compiled for bottom‐up stock modeling. Finally, the environmental impact assessment of the buildings’ demolition and disposal stage was carried out. The results showed that the building material stock was 142.31 Mt in 2017, with an increase of 69% from 2003. The reinforced concrete buildings increased rapidly from 2003 to 2017, especially in new urban areas, which has boosted demand for steel and cement by more than 150% during these 15 years. The material stock of the old urban area tends to be saturated, whereas the new urban area has experienced a rapid expansion with the material inflow four times as large as the material outflow. Potential recycling of waste concrete can reduce the generation of building demolition waste by 50%, save 0.15 km 2 of land occupation, increase raw material substitution by nearly 10 times, and reduce CO 2 emissions by 2.5 times.

Heterogeneous Fenton oxidation of 2,4-dichlorophenol catalyzed by PEGylated nanoscale zero-valent iron supported by biochar - Junlong Yu; Xiuxia Zhang; Xiaodong Zhao; Ruojun Ma; Yi Du; Shuai Zuo; Kangning Dong; Ruirui Wang; Yupeng Zhang; Yingying Gu; Juan Sun (Environmental Science and Pollution Research, 2023)

Bionic morphological design and interface-free fabrication of halfmoon microrobots with enhanced motion performance - Dong Liu; Dayin Sun; Jiaxin Zhou; Haoran Liu; Ruirui Guo; Bin Wang; Wenjun Ma; Zhenzhong Yang; Yuan Lu (Chemical Engineering Journal, 2023)

Mixotrophic culture of bait microalgae for biomass and nutrients accumulation and their synergistic carbon metabolism - Yahui Bo; Ruirui Chu; Danni Sun; Xiangyuan Deng; Chengxu Zhou; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Bioresource Technology, 2023)

A convenient paper-based fluorescent aptasensor for high-throughput detection of Pb2+ in multiple real samples (water-soil-food) - Zhiguang Suo; Ruirui Liang; Ruike Liu; Min Wei; Baoshan He; Liying Jiang; Xiaoxia Sun; Huali Jin (Analytica Chimica Acta, 2023)

Bioremediation of petroleum hydrocarbon contaminated soil by microorganisms immobilized on sludge modified by non-ionic surfactant - Junlong Yu; Ruyue Li; Xiuxia Zhang; Yi Du; Ruojun Ma; Xiaodong Zhao; Shuai Zuo; Kangning Dong; Ruirui Wang; Yupeng Zhang; Yingying Gu; Juan Sun (Environmental Science and Pollution Research, 2022)

Evaluation and analysis of heavy metals in iron and steel industrial area - Xu Zhang; Huanhuan Yang; Ruirui Sun; Meihua Cui; Ning Sun; Shouwen Zhang (Environment, Development and Sustainability, 2022)

Predicting acupuncture efficacy for functional dyspepsia based on routine clinical features: a machine learning study in the framework of predictive, preventive, and personalized medicine - Tao Yin; Hui Zheng; Tingting Ma; Xiaoping Tian; Jing Xu; Ying Li; Lei Lan; Mailan Liu; Ruirui Sun; Yong Tang; Fanrong Liang; Fang Zeng (EPMA Journal, 2022)

The severe toxicity of CuO nanoparticles to the photosynthesis of the prokaryotic algae Arthrospira sp - Xingkai Che; Ruirui Ding; Qiang Zhang; Yujie Li; Qi Sun; Yuting Li; Zishan Zhang; Wei Wang; Huiyuan Gao (Environmental Science and Pollution Research, 2021)

The participation of basolateral amygdala in the efficacy of acupuncture with deqi treating for functional dyspepsia - Ruirui Sun; Zhaoxuan He; Peihong Ma; Shuai Yin; Tao Yin; Xiaoyan Liu; Jin Lu; Yuzhu Qu; Tingting Zhang; Liuyang Huang; Xueling Suo; Du Lei; et al. (Brain Imaging and Behavior, 2021)

Overexpression of wheat α-mannosidase gene TaMP impairs salt tolerance in transgenic Brachypodium distachyon - Wenlong Wang; Yunzhen Wu; Ruirui Shi; Mengwei Sun; Qinxue Li; Guangqiang Zhang; Jiajie Wu; Yong Wang; Wei Wang (Plant Cell Reports, 2020)

Interspecific interactions in dual-species biofilms of soil bacteria: effects of fertilization practices - Xiaojie Sun; Peng Cai; Søren J. Sørensen; Monika Mortimer; Chunhui Gao; Qiaoyun Huang; Yiming Wang; Xiangui Lin; Yichao Wu; Di Zhu; Ruirui Chen (Journal of Soils and Sediments, 2020)

Ghrelin Promotes Cortical Neurites Growth in Late Stage After Oxygen-Glucose Deprivation/Reperfusion Injury - Jing Liu; Man Chen; Ruirui Dong; Changwei Sun; Shuo Li; Shigong Zhu (Journal of Molecular Neuroscience, 2019)

Quantitative monitoring of grazing intensity in the temperate meadow steppe based on remote sensing data - Dawei Xu; Baorui Chen; Ruirui Yan; Yuchun Yan; Xinbo Sun; Lijun Xu; Xiaoping Xin (International Journal of Remote Sensing, 2019)

A biophysical probe on the binding of 2-mercaptothioazoline to bovine hemoglobin - Luyi Zou; Xiaoyue Zhang; Mingying Shao; Ruirui Sun; Yuting Zhu; Binbin Zou; Zhenxing Huang; He Liu; Yue Teng (Environmental Science and Pollution Research, 2019)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

A comparison of amorphous calcium carbonate crystallization in aqueous solutions of MgCl2 and MgSO4: implications for paleo-ocean chemistry - Mei Han; Yanyang Zhao; Hui Zhao; Zuozhen Han; Huaxiao Yan; Bin Sun; Ruirui Meng; Dingxiang Zhuang; Dan Li; Binwei Liu (Mineralogy and Petrology, 2018)

Calcium carbonate precipitation by Synechocystis sp. PCC6803 at different Mg/Ca molar ratios under the laboratory condition - Zuozhen Han; Ruirui Meng; Huaxiao Yan; Hui Zhao; Mei Han; Yanyang Zhao; Bin Sun; Yanbiao Sun; Jie Wang; Dingxiang Zhuang; Wenjun Li; Lingxue Lu (Carbonates and Evaporites, 2017)

The relationship between microvasculature in white matter hyperintensities and cognitive function - Jianzhong Sun; Xinfeng Yu; Yerfan Jiaerken; Ruirui Song; Peiyu Huang; Chao Wang; Lixia Yuan; Yingying Mao; Yang Guo; Hualiang Yu; Minming Zhang (Brain Imaging and Behavior, 2017)

Genomics and expression analysis of DHHC-cysteine-rich domain S-acyl transferase protein family in apple - Meihong Sun; Xiuyan Zhao; Nan Xu; Xiaocui Luo; Yuemin Zhang; Ruirui Xu (Genes & Genomics, 2016)

Genomewide analysis of TCP transcription factor gene family in Malus domestica - RUIRUI XU; PENG SUN; FENGJUAN JIA; LONGTAO LU; YUANYUAN LI; SHIZHONG ZHANG; JINGUANG HUANG (Journal of Genetics, 2014)

Association study of a common genetic variant in pre-miR-1596 with chicken performance traits - Hong Li; Yadong Tian; Guirong Sun; Xiaojun Liu; Ruirui Jiang; Ruili Han; Guoxi Li; Xiangtao Kang (Molecular Biology Reports, 2014)

Study of the comprehensive risk analysis of dam-break flooding based on the numerical simulation of flood routing. Part I: model development - Ruirui Sun; Xiaoling Wang; Zhengyin Zhou; Xuefei Ao; Xiaopei Sun; Mingrui Song (Natural Hazards, 2014)

Study of the comprehensive risk analysis of dam-break flooding based on the numerical simulation of flood routing. Part II: Model application and results - Zhengyin Zhou; Xiaoling Wang; Ruirui Sun; Xuefei Ao; Xiaopei Sun; Mingrui Song (Natural Hazards, 2014)

DNA-A of a highly pathogenic Indian cassava mosaic virus isolated from Jatropha curcas causes symptoms in Nicotiana benthamiana - Gang Wang; YanWei Sun; RuiRui Xu; Jing Qu; ChuanSia Tee; XiYuan Jiang; Jian Ye (Virus Genes, 2014)

Eulerian–Eulerian solid–liquid two-phase flow of sandstone wastewater in a hydropower station rectangular sedimentation tank - Xiaoling Wang; Ruirui Sun; Xuefei Ao; Zhengyin Zhou; Jian Lang (European Journal of Environmental and Civil Engineering, 2013)

Cloning of TPO gene and associations of polymorphisms with chicken growth and carcass traits - Xinyan Hou; Ruili Han; Yadong Tian; Wanying Xie; Guirong Sun; Guoxi Li; Ruirui Jiang; Xiangtao Kang (Molecular Biology Reports, 2013)